2005
DOI: 10.1017/s0263034605050688
|View full text |Cite
|
Sign up to set email alerts
|

High energy heavy ion jets emerging from laser plasma generated by long pulse laser beams from the NHELIX laser system at GSI

Abstract: High energy heavy ions were generated in laser produced plasma at moderate laser energy, with a large focal spot size of 0.5 mm diameter. The laser beam was provided by the 10 GW GSI-NHELIX laser systems, and the ions were observed spectroscopically in status nascendi with high spatial and spectral resolution. Due to the focal geometry, plasma jet was formed, containing high energy heavy ions. The velocity distribution was measured via an observation of Doppler shifted characteristic transition lines. The obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 36 publications
(22 reference statements)
1
40
0
Order By: Relevance
“…The ion pulse and the laser meet with a jitter of 1 ns, peak-to-valley. In addition, a second nanosecond laser beam generated by the nhelix laser [12] is available at this location, either as a three-color probe or a second heating source up to 100 J. All three beams can be synchronized on the target with a jitter of 1 ns using the UNILAC 108 MHz clock as a timing reference.…”
Section: Overview Of the Phelix Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The ion pulse and the laser meet with a jitter of 1 ns, peak-to-valley. In addition, a second nanosecond laser beam generated by the nhelix laser [12] is available at this location, either as a three-color probe or a second heating source up to 100 J. All three beams can be synchronized on the target with a jitter of 1 ns using the UNILAC 108 MHz clock as a timing reference.…”
Section: Overview Of the Phelix Facilitymentioning
confidence: 99%
“…In 2008, first successful experiments exploited lasergenerated plasma targets for interaction experiments with heavy ions. A new experimental setup, using PHELIX additionally to the already existing nhelix laser [12], has been set up (see Fig. 8) and it quickly showed a significant improvement in the quality of the measured data.…”
Section: Experiments With Ions and Nanosecond Pulsesmentioning
confidence: 99%
“…The TARANIS laser, along with a home-built synchronized femtosecond Ti:Sapphire laser will be used in the research areas of laserfield accelerated ion generation, warm dense matter, pump-probe experiments, and X-ray lasers. Due to its high degree of flexibility TARANIS should provide an excellent tool for original scientific research as well as bench-mark investigations carried out in support of work carried out at larger external high-power laser facilities such as PALS, VULCAN, NHELIX, and others (Zvorykin et al, 2007;Jungwirth, 2005;Danson et al, 2005;Neumayer et al, 2005;Schaumann et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The status of the National Ignition Facility in the U.S and the MegaJoule project in France was the obvious focal point of interest, and is the subject of a large number of recent publications (Giorla et al, 2007;Haynam et al, 2007). However, laser laboratories worldwide are participating in the effort to understand the details of beam matter interaction physics necessary to achieve the conditions of inertial fusion (Laska et al, 2006;Lontano et al, 2006;Borghesi et al, 2005;Schaumann et al, 2005). The scientific discussion for many years shows (Meyer-ter-Vehn et al, 1990;Funk et al, 1998) and it was confirmed here that the target design is a most crucial issue for the experimental facilities as well as for a future full scale driver (Nobile et al, 2006; …”
mentioning
confidence: 57%